Maintenance Management on Prospective Duck Grouper (Cromileptes altivelis) in Aquaculture at BPBAP Situbondo - Reni, Reni; Junaedi, Abdus Salam (Sriwijaya Journal of Environment, 2024)
Duck grouper (Cromileptes altivelis) is a type of commercial fish that has a habitat on coral rocks. Duck grouper is widely consumed both domestically and abroad. Duck grouper (Cromileptes altivelis) has profitable business opportunities even though not many have cultivated it. Maintenance management of prospective duck grouper parents is one of the efforts in aquaculture to get superior quality. This activity aims to find out how and stages of maintenance for prospective grouper parents in aquaculture. This activity was carried out at the Brackish Water Aquaculture Fisheries Center (BPBAP) Situbondo. The methods used in this activity are interviews, observation, documentation, and active participation and using secondary data in the form of journals and books. Management of the breeding of prospective duck grouper parents (Cromileptes altivelis) is carried out by the stages of pond preparation, filling water in the pond, soaking prospective duck grouper parents with fresh water, stocking prospective grouper parents in aquaculture ponds, feeding, cleaning ponds, and changing water circulation. Water quality measurements were carried out three times in each week FCR results during the activity with a total of 224 fish amounting to 8.46. This activity is carried out in ponds using seawater according to its natural habitat with temperatures of 27° C, pH ranging from  8.19-8.22, salinity 34 ppt, nitrite levels ranging from 0.009-0.02 ppm, and ammonia levels ranging from 0.005-0.022 mg / L. Prevention efforts against sea leech parasites are carried out twice a month using fresh water and acriflavine.